Pollution Abatement Investment When Firms Lobby Against Environmental Regulation - Y. Hossein Farzin; Jinhua Zhao (Fondazione Eni Enrico Mattei (FEEM), 2003)
In this paper, we study a firm's optimal lobby behavior and its effect on investment in pollution abatement capital. We develop a dynamic framework where a representative firm can invest in both abatement and lobby capital in response to a possible future increase in pollution tax. We show that when the firm lobbies against the scale of the tax increase at a predetermined date, it should act like an occasional lobbyer by investing a lump-sum (optimal) amount in the lobby capital only at that date. But, to delay the new tax, it should act like a habitual lobbyer by investing continuously and at increasing rates over an optimal time period. We show that lobby expenditure crowds out investment in abatement capital and that this effect is stronger the more efficient is the lobbying activity. Further, we show that while uncertainty about the magnitude of the tax reduces the firm's incentive to lobby, uncertainty about the timing of the new tax increases it.
Keywords: H32; D81; D92; Q28; 330; Pollution Abatement; Environmental Regulation; Umweltschutzinvestition; Interessenpolitik; Umweltpolitik; Theorie